Challenges faced by registered homestay operators from the perspectives of selected stakeholders in Selangor, Malaysia - Mohamad Nor, Sarina (2019)
Ministry of Tourism, Arts and Culture (MOTAC's) homestay in Selangor encountered a decrease in the number of registered homestays because homestay operators pulled back from being registered as homestays. Increasingly, registered homestay operators went to be idle homestay business led to the all-out number of active MOTAC's homestay diminishing from 16 homestays to 13 homestays in 2016. Innovative improvements and the development of digitization are the main thrusts behind the rise and fast development of the sharing economy. The accomplishment of the sharing economy has negatively affected the traditional MOTAC homestay business operators who don't take into account these evolving patterns. Thus, this study aimed to analyze the challenges faced by registered homestay operators through the perspectives of selected stakeholders in Selangor. The challenges are examined through the lens of the disruptive innovation theory of sharing economy, including internal and external challenges in homestay business practice and whether the MOTAC’s registered homestay operators can endure the challenges ahead. This study is exploratory in nature. A mixed methods approach was applied, and methodological approach stakeholder inquiry was conducted comprising three groups: (1) Registered homestay operators (2) Unregistered homestay operators and (3) Officer of governing authorities to elicit stakeholders’ views on the homestay business. A total of 206 registered homestay operators via 15 registered homestays in Selangor were chosen from MOTAC’s list, followed by another 30 unregistered homestay operators in Klang Valley selected randomly from homestay business sites and Airbnb who use the name of "homestay". The third group is of 17 officers of governing authorities, like MOTAC and local government in Selangor, Malaysia. For the first objective, this study aims to identify the problems and challenges faced by registered homestay operators when running the homestay business. The result reveals the sharing economy like Airbnb has emerged as an alternative supplier of the conventional accommodation business models, overhauling the traditional concept of homestay business. Registered homestay operators also face internal and external challenges in homestay risks and uncertainty of transformed homestay business practice. Awareness of the monetary benefits from the collaborative economy together with the rapid growth of sharing economy and innovations in ICT have disrupted established MOTAC’s homestay business, leading to the mushrooming of unregistered homestay operators in the exciting growth market. This phenomenon is projecting a false image of a true Malaysian homestay experience to tourists and influenced many controversies, threatening the traditional homestay business, creating fierce competition in the industries and challenges by various stakeholders. This study also encounters many issues and problems such as unethical, unregistered homestay operators that may tarnish the good name of registered homestays as well as lack of homestay regulation and monitoring by the ministry, state and local government. Results of internal challenges indicate that registered homestay operators face weak homestay administration and management, lack of creativity and entrepreneurship skills lead to overdependence on outside assistance, incompetent community leadership and commitment, inadequate infrastructure facilities and conflict of interest among homestay coordinators. Realizing the good potential of homestay communitybased rural tourism (HCBRT), a few critical factors need to be taken into account, such as community capacity building and participation. Communities are more likely to support HCBRT when the perceived homestay benefits are more than the homestay costs. Therefore, the analysis of community participation levels in this study is made based on the various levels of motivation, opportunity, and ability (MOA). Hence, the second objective of this study is to investigate community capacity building and participation levels of registered homestay operators from the homestay business. The result demonstrates that the registered homestay operators face inadequate community capacity building and passive participation; lack of coordination and collaboration among homestay coordinators, homestay operators and the local community; noncompliant homestay product designing and development; instability and unavailability of investment and incentives; lack of homestay marketing approach; and limited homestay business networking. Homestay monetary adequacy is one of the inspirational factors were the homestay business capable of bringing enough profit, thus the homestay operator finds the business is worthwhile to keep going for the foreseeable future. In line with these facts, the last objective in this study attempts to measure homestay cost of operations, and revenue/income earned by registered homestay operators from homestay business. The result from the comparison of the homestay business income between registered homestay operators and unregistered homestay operators indicates there is a big gap in homestay business income generation. The average homestay income received by registered homestay operators is between RM191.00 and RM529.00 per month to the lack of homestay tourist arrivals, whereas compared with the average unregistered homestay operator’s income is between RM4,000.00 and RM15,000.00 without homestay activity depending on the season. This study reveals not all registered homestay operators who engaged in homestay business received a good income after a long involvement in the homestay business. In this manner, increasingly registered homestay operators are becoming demotivated, hesitant to give full commitment and prone to pull back when they see little advantage and no adequate income generated from being a registered MOTAC homestay. The overall findings of this study offer some recommendations to improve existing guidelines on homestay business for authorities, particularly MOTAC and local authorities who give licenses for homestay business. Lodging houses business for all residential apartments, condominium, flats, and the gated private house should be regulated and must operate the homestay business with the license irrespective of whether they use “homestay” or not in promoting their homestay business. Hence, the findings in this study may contribute to the importance of homestay business sharing economy via collaborative economy model among homestay stakeholders that gives an energy practice of the longevity of the traditional homestay business in an effort to serve the customer better from competition to network collaboration.